Perioperative management of a patient with a giant thyroglossal duct cyst: a case report. Issue 6 (30th June 2022) - Iwasa, Yoh-ichiro; Hori, Kentaro; Hiramatsu, Ken; Yokota, Yoh; Kitano, Tomohiro; Kitoh, Ryosuke; Takumi, Yutaka
Abstract: Thyroglossal duct cysts (TGDC) are the most common type of congenital neck masses, which generally present in young adults. We present a rare case of a giant TGDC in a 77-year-old patient who required atypical perioperative management. The patient presented with a large soft mass on his anterior neck. Computed tomography showed a lobulated cystic mass measuring 18 × 16 cm, extending from the tongue base to the inferior level of the clavicle. Because difficult intubation was expected, the cyst was punctured and most of the fluid was drained prior to surgery. The swelling of the tongue base was remarkably reduced, and intubation was performed safely. The cyst was extracted using the Sistrunk procedure and tracheotomy was performed. Histopathological examination confirmed the diagnosis of TGDC. Preoperative volume reduction of the cyst and tracheotomy should be considered for oral intubation and postoperative airway management, respectively, in patients with large TGDC.